Global Regulatory Agencies and Data Transparency. Issue 3 (2021) - Plott, Caroline F.; Sharfstein, Joshua M.
Abstract: Egilman et al. review the current data sharing practices of three global regulatory agencies — Health Canada, the European Medicines Agency and the Food and Drug Agency. While there has been progress towards increasing transparency over the past decade, progress has been slow.